INFLUENCE OF THE HARVESTER OPERATION MODE ON ERGONOMIC PARAMETERS OF OPERATORS - Ferreira do Nascimento Santos, Diego Weslly; Magalhães Valente, Domingos Sarvio; Fernandes, Haroldo Carlos; Ribeiro Furtado Júnior, Marconi; Mariano Leite, Daniel (Floresta, 2022)
Changes in the way of operating forest machines causes a reduction in fuel consumption, however it can affect ergonomic factors of the operators. Thus, the objective of this research was to evaluate ergonomic parameters of the operation with harvester in different modes of operation. The operating modes were obtained by changing the engine speed and flow rate of the hydraulic pump. The machine was programmed to operate at engine speeds of 2,060; 2,000; 1,950; and 1,900 rpm and hydraulic pump flow of 300; 295; 290 l min-1, totaling 12 operating modes. The research was carried out on the average tree volumes of 0.08; 0.12; and 0.16 m³ tree-1. The Acceleration values resulting from normalized exposure (Aren) and the TOR (Real Occupancy Rate) - TOMCAR (Maximum Occupancy Rate considering Repetitive Activities) were measured. The data were submitted to analysis of variance and when significant compared by the Tukey test. Changes in the machine's operating mode cause significant decreases in Aren values. A execução da operação deslocamento e busca expõem os operadores aos maiores valores de aceleração resultante de exposição normalizada. A operação com harvester se caracteriza como causadora de doenças ocupacionais. The execution of the displacement and search operation exposes operators to the highest values of acceleration resulting from normalized exposure. The operation with harvester is characterized as causing occupational diseases.